2013
DOI: 10.1680/jees.2013.0061
|View full text |Cite
|
Sign up to set email alerts
|

Tetracycline degradation by ozonation, and evaluation of biodegradability and toxicity of ozonation byproducts

Abstract: Tetracycline was exposed to ozone by bubbling at different pH levels, and the acute toxicity of ozonation byproducts was tested by luminescent bacteria (Vibrio qinghaiensis sp.-Q67). Residual tetracycline in the solutions was detected by high performance liquid chromatography (HPLC). The results indicated that tetracycline was immediately degraded by ozonation and the degradation was favored at higher pH. Tetracycline (20  mg L−1) was completely degraded after 5  min of ozonation. However, total organic carbon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…The gentle increase of COD removal efficiency during the reaction process may result from the intermediates formed which were more stable than tetracycline under the experimental conditions. The similar phenomenon was reported by Wu et al [27] when tetracycline was degraded by ozone. They found that only 15% COD of tetracycline was removed by the first 5 min and the COD removal was not increased by extending the reaction time to 20 min.…”
Section: The Changes Of Cod Biodegradability and Active Toxicity Witsupporting
confidence: 86%
See 3 more Smart Citations
“…The gentle increase of COD removal efficiency during the reaction process may result from the intermediates formed which were more stable than tetracycline under the experimental conditions. The similar phenomenon was reported by Wu et al [27] when tetracycline was degraded by ozone. They found that only 15% COD of tetracycline was removed by the first 5 min and the COD removal was not increased by extending the reaction time to 20 min.…”
Section: The Changes Of Cod Biodegradability and Active Toxicity Witsupporting
confidence: 86%
“…The intermediates were further oxidized with the progress of ozonation, which led to the increasing D. magna mortality [50,51] and the inhibition ratio reached 95%. The similar tendency was reported by Wu [27] and Beltrán [52] when tetracycline and sulfamethoxazole were oxidized by ozone, respectively. They found the more toxic by-products were formed during ozonation process compared with the target pollutants.…”
Section: The Changes Of Cod Biodegradability and Active Toxicity Witsupporting
confidence: 85%
See 2 more Smart Citations
“…The acute toxicities of the soil extracts were tested by the luminescent assay of V. qinghaiensis sp.-Q67 kit in accordance with our previous method (Wu et al 2010). The toxicity assays were performed in triplicates.…”
Section: Toxicity Assaymentioning
confidence: 99%